Improving Students’ Reading Comprehension Through Text Structure Tasks - Abdul Rohman (Script Journal: Journal of Linguistics and English Teaching, 2017)
Reading skill is one of the four main language skills taught in the classes of the English Department of Faculty of Education of Islamic University of Malang (FKIP Unisma). As the result of teaching reading had not achieved satisfactory result, the researcher conducted a study to find out how texts structure tasks can improve the students’ reading comprehension.            The method employed in this research was a classroom action research. It comprised four phases: planning, implementation, observation and reflection. The steps were adopted from Kemmis and Taggart’s action research model (1988). The subjects of the study were the four semester students of the English Department of FKIP Unisma in 2006 academic year. In the procedures and implementation process, one cycle consisting of four actions was done.            The instruments used in the study were observation sheets and test. The observation sheets were made two forms. One form of observation sheets was to observe the teacher in implementing the action and the other observation sheets were used to observe the students’ activities or reaction to the teachers’ activities during the learning-teaching process. The second instrument used was a test. It was to evaluate the effectiveness of the strategy used.After four actions were conducted, a test was given to the students. The test result showed that the students’ mean score was 75.88 and the lowest score the students obtained was 65. The researcher decided that no more cycle was needed for the study had met the criteria of success. The action was considered successful if the students’ mean score reached 75 or under the category of B+, and the lowest score the student obtain was not less than 65.00.